2014
DOI: 10.1016/j.nima.2014.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of solid-state thermal neutron detectors based on hexagonal boron nitride epilayers

Abstract: Solid-state thermal neutron detectors with improved detection efficiencies are highly sought after for many applications. Hexagonal boron nitride (hBN) epilayers have been synthesized by metal organic chemical vapor deposition on sapphire substrates. Important material parameters including the mobility-lifetime (μτ) product and the thermal neutron absorption length (λ) have been measured. For hBN epilayers with a room temperature resistivity of 5.3 Â 10 10 Ω cm, the measured μτ product of electrons is 4.46 Â 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
66
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 28 publications
(61 reference statements)
1
66
0
2
Order By: Relevance
“…7,8 With its large thermal neutron cross-section, h-BN is also a promising material for realizing high efficiency and low cost solid-state neutron detectors. 9,10 Our knowledge concerning the band structure and optical properties of h-BN is limited. In spite of the recognition of the importance of h-BN for emerging applications, many of its fundamental physical properties are still unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 With its large thermal neutron cross-section, h-BN is also a promising material for realizing high efficiency and low cost solid-state neutron detectors. 9,10 Our knowledge concerning the band structure and optical properties of h-BN is limited. In spite of the recognition of the importance of h-BN for emerging applications, many of its fundamental physical properties are still unknown.…”
mentioning
confidence: 99%
“…[7][8][9][10] Epitaxial h-BN layers with high optical qualities can be achieved, 7,20 but these materials generally lack the intrinsic FX transitions above 5.7 eV due to the presence of native and point defects. 7,20 Most recent studies have suggested that the D-series emission lines are due to the recombination of excitons bound to deep acceptors formed by carbon impurities occupying the nitrogen sites, and h-BN epilayers exhibiting pure intrinsic FX emission can be obtained by growing the materials under high ammonia flow rates.…”
mentioning
confidence: 99%
“…Hexagonal boron nitride (h-BN), a wide bandgap ($6.5 eV) semiconductor, known for its deep ultraviolet photonic applications, [1][2][3][4][5][6][7] has emerged as an outstanding neutron detector material [8][9][10][11][12][13][14] due to the fact that the B-10 ( 10 B) isotope has a large capture cross section for thermal neutrons (3840 b or 3.84 Â 10 À21 cm 2 ). Special nuclear materials (SNMs) tend to emit neutrons through fission reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, solid-state neutron detectors that have the performance of 3 2 He detectors without their drawbacks are highly soughtafter technologies. [8][9][10][11][12][13][14][16][17][18][19][20][21][22] As a semiconductor, the density of atoms that can interact with thermal neutrons in 100% 10 B-enriched h-BN [N( 10 B) ¼ 5.5 Â 10 22 /cm 3 ] is about 550 times higher than that in He-3 gas pressurized at 4 atm, providing an absorption length (k) of thermal neutrons in h- 10 BN of only 47 lm, where k ¼ (3.84 Â 10 À21 cm 2 Â 5.5 Â 10 22 /cm 3 ) À1 ¼ 0.0047 cm. 13,14 This length scale is negligibly small compared to the diameters of typical 3 2 He detectors.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The large thermal neutron capture cross-section (3840 barns) of 10 B 10,11 also makes hBN potentially a very promising material for the realization of solid-state neutron detectors. 12,13 The knowledge and experimental data on the electrical transport properties of hBN are scarce due partly to its very large bandgap and highly electrical insulating nature. An improved understanding of the electrical properties of hBN is necessary to take the advantages of its excellent physical properties for significant device applications.…”
Section: Introductionmentioning
confidence: 99%